1999
DOI: 10.1177/026988119901304s04
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Severe Insomnia In The General Population: Results of a European Multinational Survey

Abstract: The epidemiology of severe insomnia and its effect on quality of life and healthcare consumption was assessed in a survey of the general population of five northern European countries. Applying established consumer sampling techniques, insomnia sufferers were selected from the general population using a questionnaire, conducted by face-to-face interview, and severity of insomnia was ranked (severe, mild/moderate, no sleep complaint) using a specific algorithm. Population samples were matched according to case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
68
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(79 citation statements)
references
References 9 publications
9
68
1
1
Order By: Relevance
“…Since the study population was young adults attending a university, effects of age on sleep disturbances could not be found. Like in many studies showing that sleep disturbances are found more frequently among women than men (7)(8)(9)(10)(11)(12), it was found in this study that the female students slept slightly shorter and reported more sleep disturbances than their male counterparts.…”
Section: Discussionsupporting
confidence: 73%
“…Since the study population was young adults attending a university, effects of age on sleep disturbances could not be found. Like in many studies showing that sleep disturbances are found more frequently among women than men (7)(8)(9)(10)(11)(12), it was found in this study that the female students slept slightly shorter and reported more sleep disturbances than their male counterparts.…”
Section: Discussionsupporting
confidence: 73%
“…He confirmed that stress, and in particular stress originating from the home, is the main determinant of the presence of insomnia. The greatest prevalence of insomnia in the group of previously married individuals was verified in other populational studies 10,12,14,22 . Bixler 27 observed in Los Angeles a strong association between loneliness and insomnia, which is perhaps a common aspect in previously married individuals.…”
Section: Discussionsupporting
confidence: 64%
“…[15][16][17] and international 10,12,14,18,22,23 publications. This leads us to speculate about the involvement of hormonal factors.…”
Section: Discussionmentioning
confidence: 99%
“…Among women and widowers or separated people, the prevalence of BDZ use was significantly higher. In Switzerland 29 , 7% of use of hypnotic drugs was found without a medical prescription in groups of chronic insomniac people with ages from 20 to 21 years old and 12% in the group from 27 to 28 years of age. A Brazilian general population survey 3 detected 14.6% of hypnotic drug use in the last month, twice as much as in this paper.…”
Section: Discussionmentioning
confidence: 99%